PROPOSED PRODUCTION IMPROVEMENT BY MINIMIZING THE NUMBER OF REJECT PACKAGING OF DRUG TABLETS DUE TO DEFECTS IN PACKING (CARTONING) MACHINE USING THE SIX SIGMA METHOD APPROACH AT PT. XYZ - Fathin Nur Aeni (Journal of Industrial Engineering Management, 2023)
This research focuses on process improvement through analysis of quality control of the packing process using packing machines (cartoning) to reduce the number of rejected containers so as to reduce company losses with the Six Sigma method approach with the stages of Define, Measure, Analyze, Improve (DMAI).